Consumer personality, attitudes and preferences in out-of-home contexts: The case of rosé wine in Italy. Issue 1 (11th March 2019) - Capitello, Roberta; Bazzani, Claudia; Begalli, Diego
Abstract : Purpose: This study aims to focus on consumers' preferences towards rosé wine and explore whether and how the consumption context may influence consumers' choices. Design/methodology/approach: Using social networks platform, the authors conducted a choice experiment, to evaluate Italian consumers' preferences for a glass of rosé in two consumption contexts, restaurant and wine bar. Characteristics of the rosé wine also included price, origin and type of wine. The authors applied a latent class analysis to define rosé wine consumers' segments and incorporated personality traits in the model. Findings: The results define three rosé wine drinkers' profiles: "Wine bar visitors", "The unenthusiastic" and "Restaurant visitors". Socio-demographic characteristics and personality traits significantly affect consumers' membership to the different segments. Who prefers to drink a rosé glass at the wine bar is younger, more opened to new experiences and, therefore, more inclined towards more sophisticated choices. Consumers at the restaurants tend to be more extrovert and sensitive to price. Practical implications: This study offers insight for practitioners of both wine and hospitality industries in the development of strategies for new products market placement and, at the same time, for academics who are interested in the understanding of behavioural reasoning of consumers' wine purchase choices. Originality/value: This research investigates the effect of consumption context on individuals' preference formation for a less familiar wine, such as rosé in Italy. To the authors' knowledge, no previous studies explored how personality traits may affect consumers' wine consumption context choices.